A progress report on the crystallographic studies on the B800–850 antenna complex from Rhodopseudomonas acidophila strain 10050. (February 1993) - Cogdell, Richard J.; Halloren, Evelyn; Hawthornthwaite, Anna M.; Thunnissen, Marjolein M. G. M.; Freer, Andy A.; McDermott, Gerry; Guthrie, Neil; Isaacs, Neil; Lindsay, J. Gordon; Papiz, Miroslav
Abstract : Summary Large single crystals (up to 1 mm in each dimension) of the B800–850 antenna complex from Rhodopseudomonas acidophila strain 10050 have been grown in the presence of β-octyl-glucoside. These crystals have the space group R32 and unit cell dimensions of a = b = 119.9 Å and c = 297.0 Å. Recently we have improved our crystallization procedures so that all crystals now diffract reliably to beyond 3.5 Å, with some diffracting to below 3 Å. A range of isomorphous heavy atom derivatives have been prepared and we are now engaged in locating the heavy atom sites within the unit cell.